Factors associated with the breastfeeding status of babies aged 0-7 days in Bengkulu City: Abstract, introduction, methods, results, discussion, conclusions, thanks, bibliography. - Febriani, Cantika Alya Dwy; Wati, Nopia; Oktavidiati, Eva; Kosvianti, Emi; Pratiwi, Bintang Agustina (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Abstract Background: Bengkulu Province has 10 regencies/cities of which 9 regencies/cities experience fluctuating breastfeeding coverage, one city, Bengkulu City, has experienced a decline in exclusive breastfeeding coverage in the last 3 years by 60.5%, 60%, 43.66% (2020-2022). This study aims to identify the factors of maternal age, education, occupation, knowledge, attitude and self-efficacy associated with breastfeeding patterns of infants aged 0-7 days in Bengkulu City Method: The method used was a quantitative-based study with an observational analytic descriptive approach and case control design. The study sample included 62 mothers with newborns aged between 0 to 7 days who live in Bengkulu City. The participants were divided into two groups: a case group consisting of 31 mothers who did not breastfeed in the first three days after delivery, and a control group consisting of 31 mothers who breastfed in the first three days after delivery. . Data were collected through interviews and questionnaires and analyzed using the chi-square test Results: The findings showed no significant association between maternal age p=0.310 (>0.005), education p=1 (>0.005), occupation p=0.449 (>0.005), knowledge p=0.198 (>0.005), attitude p=1 (>0.005), and maternal self-efficacy p=0.779 (>0.005) with breastfeeding status. This study emphasizes the need for special strategies and efforts to improve breastfeeding, in the Bengkulu City area. Conclusion: In conclusion, this study found no significant association between the variables of maternal age, employment status, educational background, knowledge, attitude, and self-efficacy with exclusive breastfeeding practices. These results emphasise the importance of interventions that target not only knowledge, but also mothers‘ attitudes and beliefs regarding breastfeeding, as well as providing appropriate support based on mothers’ employment conditions and age to improve breastfeeding success rates.